Parental Role in Digital Era Character Formation: A Deuteronomy 6:4-9 Perspective - Dahliana Purba , Nursenta; Oktarin Colia Sembiring , Elby Dinant (Jurnal Didaskalia, 2025)
The digital transformation has fundamentally altered family dynamics and child development patterns, creating unprecedented challenges for moral and spiritual formation within contemporary families. While technology offers substantial benefits, unregulated digital exposure poses significant risks to children's character development and spiritual growth. This study examines the critical role of parents in fostering moral and spiritual development among family members during the digital era, utilizing biblical principles from Deuteronomy 6:4-9 as a theoretical framework. A systematic literature review methodology was employed, analyzing peer-reviewed publications from 2018-2024 focusing on parental influence, digital era challenges, and family-based character formation. Data were synthesized using thematic analysis to identify key patterns and relationships between parental practices and child development outcomes. The analysis reveals that intentional parental engagement significantly correlates with positive character formation outcomes in children exposed to digital environments. Effective parental strategies include structured digital literacy education, consistent moral guidance, and active spiritual mentorship. Families implementing comprehensive digital stewardship approaches demonstrated superior outcomes in children's moral reasoning, spiritual development, and behavioral regulation compared to families with minimal parental involvement. Parents serve as primary architects of family moral and spiritual development, particularly in navigating digital era complexities. The integration of biblical principles with contemporary parenting strategies provides a robust framework for character formation. This study contributes to the growing body of evidence supporting proactive parental involvement as essential for optimal child development in technologically saturated environments.